Business guide to the General Agreement on Trade in Services - International Trade Centre UNCTAD/WTO (ITC GenevaCH, 2000)
Provides a guide to the General Agreement on Trade in Services (GATS) and the key features of the multilateral system of trade rules covering services. Examines rights and benefits conferred and obligations imposed by GATS on the business community and governments; and, implications for developing countries and economies in transition. Identifies main opportunities and challenges encountered at the practical business level in the implementation of GATS rules and market access commitments.